Упругое рассеяние дейтронов с энергией 13,6 Мэв на легких ядрах - Верещагин А. Н.; Коростова И. М.; Немец О. Ф.; Соколов Л. С.; Токаревский В. В.; Чернов И. П. Иван Петрович (1967, 1967)
В фонде НТБ ТПУ отсутствует